Opiate modulation of the pituitary-adrenal axis: effects of stress and circadian rhythm. - Grossman, A; Gaillard, R; McCartney, P; Rees, L; Besser, G (1982)
The opiate control of the pituitary-adrenal axis has been investigated in normal subjects. The infusion of 1 mg of the met-enkephalin analogue, DAMME, led to a fall in circulating cortisol in spite of a fall in blood pressure. Conversley, 16 mg of the opiate antagonist, naloxone led to brisk and pronounced elevations in plasma ACTH, lipotrophin (LPH) and cortisol. The rise above basal levels was consistent, irrespective of whether the infusion was given at 09.00, 18.00, or 23.00 h; the peak response obtained was significantly less at 23.00 h than at either 09.00 or 18.00 h. Finally, insulin-induced hypoglycaemia (0.15 u/kg) or naloxone (25 mg) produced a similar rise in plasma cortisol which was no different when the two stimuli were combined. It is suggested that there is a constant tonic inhibition of the pituitary-adrenal axis by endogenous opiates throughout 24 h, and that the circadian rhythm of ACTH/LPH secretion is not due to changes in opiate tone. However, disinhibition of this tone is likely to be responsible, at least in part, for the rise in cortisol in response to hypoglycaemic stress.